The drowned landscapes of Eeyou Istchee: 50 years of archaeology in the context of hydroelectric development - Denton, David (Archéologiques)

(untitled) (Association des archéologues du Québec, 2026)
This paper reflects on fifty years of archaeological research carried out in Eeyou Istchee in the context of hydroelectric development associated with the La Grande Complex. Salvage archaeology programs undertaken since the early 1970s have documented thousands of sites and produced an exceptional archaeological archive recording millennia of human occupation in the region, including the long history of Iiyiyuu-Iinuu use of these lands. Drawing on a series of vignettes from sites now submerged beneath different reservoirs, the paper highlights the archaeological and historical richness of these cultural landscapes. It also examines the evolving relationship between archaeology and Cree communities, from the early salvage programs associated with large hydroelectric projects to more collaborative initiatives developed in recent decades. Finally, it challenges the assumption that reservoirs constitute archaeological “dead zones” and argues for improved accessibility to the archaeological archive, the establishment of monitoring programs in drawdown zones, and the fuller integration of archaeological heritage into contemporary processes of reconciliation.